A Statistical Note on the Religiosity of Persons with Disabilities - Hendershot, Gerry (Disability Studies Quarterly, 2006)
Indicators of the religiosity of persons with and without disability are compared using statistics from the National Survey of Family Growth, which represents community-dwelling persons of reproductive age in the U.S. It is found that persons with disabilities are less likely than persons without disabilities to attend religious services and less likely to report that religion is important in their daily lives.